Sobre aprender e ensinar matemática: internet, sala de aula e experiências outras - Mendes, Ricardo de Oliveira [UNESP] (2017)
This PhD research is related to teaching and learning mathematics with a view in "experiences" in an introduction to Differential and Integral Calculus and its applications course offered to the Biological Sciences undergraduate course of Universidade Estadual Paulista - Rio Claro Campus. As a support to the classes, the researcher developed a website with the content of the syllabus which was widely used during the classes. The research started qualitative, focusing on the potential of digital technologies in school education. But in the progress of its development, it was building up from the clues of cartography, and therefore digital technology was no longer the focus of research, giving rise to questioning teaching and learning mathematics. In this work, teachers and students are understood not as active subjects and responsible for the educational process, but as subjects of experience. Subjects who suffer and expose their bodies to meetings. In this way, the learning and teaching referred here are closer to the exercise of potentiate the ability to affect and be affected by each encounter. It is, therefore, a learning that has nothing to do with developing skills or acquiring knowledge. Similarly, a teaching that has nothing to do with transmitting, mediating, facilitating or sharing knowledge. It is a teaching and a learning that are not owned by anyone and only make sense in the current events.